Lung cancer in HIV infected patients: facts, questions and challenges. Issue 11 (27th October 2006) - Cadranel, J; Garfield, D; Lavolé, A; Wislez, M; Milleron, B; Mayaud, C
Abstract : AIDS related mortality has fallen sharply in industrialised countries since 1996 following the introduction of highly active antiretroviral therapy. This has been accompanied by an increase in the proportion of deaths attributable to non-AIDS defining solid tumours, especially lung cancer. The risk of developing lung cancer seems to be higher in HIV infected subjects than in the general population of the same age, partly because the former tend more frequently to be smokers and, especially, intravenous drug users. The carcinogenic role of the antiretroviral nucleoside drugs and their interaction with smoking needs to be examined. Interestingly, there is no clear relationship between the degree of immunosuppression and the risk of lung cancer, so the reason for the increased risk is unknown. The mean age of HIV infected patients at the time of lung cancer diagnosis is 45 years and most are symptomatic. Lung cancer is diagnosed when locally advanced or metastatic (stage III–IV) in 75–90% of cases, similar to patients with unknown HIV status. Adenocarcinoma is the most frequent histological type. The prognosis is worse in HIV infected patients than in the general lung cancer population. Efficacy and toxicity data for chemotherapy and radiation therapy are few and imprecise. Surgery remains the treatment of choice for localised disease in patients with adequate pulmonary function and general good health, regardless of immune status. Prospective clinical trials are needed to define the optimal detection and treatment strategies for lung cancer in HIV infected patients.